The elements of service quality which contributes to customer satisfaction in using TM services in Seremban / Norizzati Abdul Hamid - Abdul Hamid, Norizzati (Faculty of Business and Management, 2007)
This study mainly focusing on the elements of service Quality provides by TM Seremban which contributes to Customer Satisfaction in using the services. This study requires 60 respondents to answer the questionnaire in order to help the researcher to get the findings. The respondents that answer the questionnaire were based on probability sampling which apply the sample random technique. There were mainly focus on customer that stay in Taman Pinggiran Golf who already the existing TM customer and have the experience in using TM Point services.